Enhancing landfill gas bio-desulfurization: operational insights and microbial dynamics from the Daegu Bangcheon-ri Sanitary Landfill - Cho, Eunsue; You, Young-Hyun; Back, Chang-Gi; Hong, Ji Won (Frontiers in Environmental Science, 2024)
This study evaluates the efficacy of the Thiopaq bio-desulfurization system at the Daegu Bangcheon-ri Sanitary Landfill in Korea over one year focusing on operational insights and microbial dynamics. The system employs sulfur-oxidizing bacteria (SOBs) to convert hydrogen sulfide (H2S) in landfill gas (LFG) into elemental sulfur. Key findings include maintaining over 96% H2S removal efficiency despite operational challenges such as sulfur clogging and foam formation. Significant microbial community shifts were observed, with Thioalkalibacter halophilus remaining robust, Alkalilimnicola ehrlichii declining, and Halothiobacillus kellyi becoming more prominent, especially during new well installations with high thiol (methanethiol) concentrations. Scanning electron microscopy revealed distinct morphological characteristics of bio-sulfur under varying conditions contributing to process optimization. Our results underscore the necessity for continuous monitoring and adaptive management of microbial populations and system parameters to effectively handle fluctuating LFG compositions and operational conditions. This study provides substantial guidance for enhancing LFG quality and bio-sulfur production in large-scale landfills.